2001
DOI: 10.1152/ajpheart.2001.280.2.h642
|View full text |Cite
|
Sign up to set email alerts
|

Carotid baroreflex pressor responses at rest and during exercise: cardiac output vs. regional vasoconstriction

Abstract: The arterial baroreflex mediates changes in arterial pressure via reflex changes in cardiac output (CO) and regional vascular conductance, and the relative roles may change between rest and exercise and across workloads. Therefore, we quantified the contribution of CO and regional vascular conductances to carotid baroreflex-mediated increases in mean arterial pressure (MAP) at rest and during mild to heavy treadmill exercise (3.2 kph; 6.4 kph, 10% grade; and 8 kph, 15% grade). Dogs (n = 8) were chronically ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
65
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 28 publications
10
65
1
Order By: Relevance
“…Although the major target vascular bed(s) for this increased peripheral vasoconstriction with metaboreflex activation after SAD were not revealed in the present study, previous observations from our laboratory (3,20) have shown that, as workload increases, vasoconstriction in active skeletal muscle becomes a progressively more important component of the pressor response to carotid occlusion. Indeed, as skeletal muscle blood flow becomes a progressively larger fraction of CO, the potential ability of this vascular bed to regulate arterial pressure also increases proportionally (15), and at high workloads the majority of the carotid pressor response is due to vasoconstriction in the active skeletal muscle.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Although the major target vascular bed(s) for this increased peripheral vasoconstriction with metaboreflex activation after SAD were not revealed in the present study, previous observations from our laboratory (3,20) have shown that, as workload increases, vasoconstriction in active skeletal muscle becomes a progressively more important component of the pressor response to carotid occlusion. Indeed, as skeletal muscle blood flow becomes a progressively larger fraction of CO, the potential ability of this vascular bed to regulate arterial pressure also increases proportionally (15), and at high workloads the majority of the carotid pressor response is due to vasoconstriction in the active skeletal muscle.…”
Section: Discussioncontrasting
confidence: 61%
“…As observed previously, in normal animals the major mechanism utilized by the muscle metaboreflex to raise arterial pressure during submaximal exercise is an increase in CO, with little if any net change in peripheral vascular conductance to nonischemic areas (16,18,39). This increase in arterial pressure is attenuated by arterial and cardiopulmonary baroreflexes (3,32). However, the arterial baroreflex not only modifies the strength of the muscle metaboreflex but markedly changes the mechanisms mediating the muscle metaboreflex pressor response.…”
Section: Discussionmentioning
confidence: 58%
“…Thus the arterial baroreflex buffers the muscle metaboreflex mainly by preventing peripheral vasoconstriction. This is consistent with studies in canines as well as in humans showing that unloading of the arterial baroreceptors during exercise raises arterial pressure mainly via peripheral vasoconstriction (13,80). In heart failure, the strength of the arterial baroreflex is depressed and sinoaortic denervation neither markedly increases the magnitude nor alters mechanisms of the metaboreflex pressor response; a somewhat larger rise in arterial pressure occurs via even more peripheral vasoconstriction (48,49).…”
Section: Impaired Baroreflex Buffering Of Muscle Metaboreflex In Hearsupporting
confidence: 89%
“…In addition, the majority of these studies used pharmacological approaches to examine arterial baroreflex function, which do not permit an assessment of BP responses to baroreflex perturbation. Thus, to date, no studies have investigated whether there are sex-related differences in BP responses elicited by the arterial baroreflex.Previous studies (12,41,42) have suggested that alterations in vasomotor activity are the primary means by which the arterial baroreflex regulates BP. In dogs, the pressor response to carotid sinus hypotension via bilateral carotid occlusion was mediated solely by changes in TVC (12).…”
mentioning
confidence: 99%
“…Previous studies (12,41,42) have suggested that alterations in vasomotor activity are the primary means by which the arterial baroreflex regulates BP. In dogs, the pressor response to carotid sinus hypotension via bilateral carotid occlusion was mediated solely by changes in TVC (12).…”
mentioning
confidence: 99%